Time-controlled hierarchical multikeyword search over encrypted data in cloud-assisted IoT - LIU, Tong (Institutional Knowledge at Singapore Management University, 2022)
Internet of Things (IoT) devices and systems are becoming increasingly commonplace, and as such systems scale up, so do the computational and storage requirements. Hence, one recent trend is to outsource data from IoT devices to remote systems. To facilitate both ciphertext retrieval and data confidentiality in the outsourced data, a number of searchable encryption (SE) approaches have been proposed in the literature. However, due to limited keyword space, a number of SE schemes are vulnerable to keyword guessing attacks (KGAs). In addition, existing SE approaches generally do not consider the hierarchical structure in which users at different levels require varying access privileges. Furthermore, existing SE schemes seldom provide time-controlled access control. Therefore, in this article, we propose a time-controlled hierarchical multikeyword search by using a double-server architecture to mitigate KGA. In our approach, we also build a public key tree to support different access permissions for hierarchical users. Formal security analysis shows that our scheme is secure, and extensive experiments demonstrate that our scheme is practical.